(untitled) (Sebha University Conference Proceedings, 2022)
Corruption in general is a complex and complex phenomenon, which includes imbalances that affect the political, economic, social, moral and ethical aspects of society, which need concerted efforts to address and get rid of it. The issue of corruption is not the result of today or yesterday, but rather the result of a number of cumulative factors and causes, and it has become a serious danger to all the institutions of society. Therefore, the phenomenon of corruption must be studied and how to confront it through the various means of education and set educational priorities to combat it. Hence, the current study, which aims to define the concept of societal corruption, investigate the phenomenon, its causes and effects, and then clarify the role of educational institutions in combating this phenomenon so that it can be confronted, reduced, and possibly eliminated.